Simulation analysis for multicast context delivery network mobility management - Mohd Aman, Azana Hafizah; Hassan Abdalla Hashim, Aisha; Mohd Ramli, Huda Adibah (Institute of Advanced Engineering and Science (IAES), 2017)
Abstract The objective of this paper is to presents analyses for multicast network mobility management using NS3. It is mainly to verify the proposed network architecture and its activities. NS3 is a network simulator that implements virtually network prototype that is close to real implementation. Network mobility management has become a popular topic in networking research due to its ability to mitigate mobile IPv6 problems. However the standard network mobility management only introduced to support unicast traffic. Hence this paper integrates context transfer and multicast fast reroute, and implements this integration to the standard network mobility management. This implementation enables multicast to network mobility management with high network performance support. The analyses focus on the throughput performance. The analyses of this simulator are hereby presented. Keywords: Multicast, Network Mobility, Mobile Multicast, Network Mobility Management